Synthesis of the Enantiomers of Thioridazine - Antonsen, Simen; Monsen, Erling B.; Ovchinnikov, Kirill; Nolsøe, Jens M. J.; Ekeberg, Dag; Kristiansen, Jette E.; Diep, Dzung B.; Stenstrøm, Yngve (SynOpen, 2020)
Thioridazine, a well-known antipsychotic drug, has shown promising effects on several bacterial strains (including Mycobacterium tuberculosis and methicillin-resistant Staphylococcus aureus). Suppressive effects towards selected cancer cell-lines have also been reported. However, due to adverse effects, the compound is no longer in use for the primary indication. More recent research has demonstrated that these side effects are limited to one of the two enantiomers, (+)-thioridazine. The question arises to whether the beneficial effects of thioridazine are limited to one enantiomer, or if (–)-thioridazine can prove itself to be useful in its pure enantiomeric state. The published procedures on the synthesis of the optically pure enantiomers of thioridazine were found to be unsatisfactory, either due to low optical purity, high cost, or problems scaling up. Herein, we have used an auxiliary-based strategy for the total synthesis of both enantiomers in high optical purity and good overall yield. The strategy can easily be scaled up. Both enantiomers were tested against several bacteria. Comparison of the racemic mixture, (–)-thioridazine and its (+)-antipode revealed that they have the same antimicrobial effects. Thus, the non-toxic enantiomer, (–)-thioridazine, can prove useful in this role and should be investigated further.
Keywords: thioridazine; antibacterial; enantiomers; total synthesis; sulfinyl aldimines